Teacher’s Perception toward the Readiness to Face Multiculturalism in Arabic Teaching and Learning - Noza Aflisia; Mohamad Erihadiana; Nur Balqis (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2020)
Multicultural presence required an appropriate response from Arabic teachers, so that Arabic is easily accepted and loved by various groups. This research aimed to analyze the efforts of Arabic teachers in dealing with multiculturalism and analyze the obstacles encountered in applying multicultural education in Arabic language learning. This qualitative descriptive research was conducted with interview and documentation. While the data analysis and processing techniques used in this study were processing and preparing the data for analysis, reading the entire data, starting coding all the data, coding to explain the settings, people, categories, themes analyzed, and describing the themes that will be presented again in the narrative/qualitative report. The results revealed that the efforts of Arabic teachers to confront multicultural were by reaffirming the unifying Arabic for Muslims, confirming Arabic as one of the International language, learning the essence of multicultural, improving didactic and methodical competencies, attending training, and modeling. The constraints of the application of multicultural education in Arabic language learning were lack of understanding of the essence of multicultural, lack of knowledge of learning methods and strategies, lack of literature, lack of syllabus and teaching materials contained multicultural education, lack of support from institutions, and lack of training and guidance.